임상적 통계를 통한 홍채진단의 신빙성 연구 - 김경수(Kyong Su Kim); 박병민(Byong Min Park); 차용석(Yong Seok Cha); 김용정(Yong Jeong Kim); 윤종민(Jong Min Yun); 이승언(Seung Eon Lee); 차숙(Suk Cha); 김강산(Kang San Kim) (동의생리병리학회지, 2003)
This Study was carried out for proof of confidence of Iris Diagnosis. We analyzed relation between Iris Signs and Chief Complain, and then analyzed relation between Iris Signs and Past History. The rate of relation between Iris Signs and Chief Complain was 72.1 %. The rate of relation between Iris Signs and Past History was 52.9%. synthetically, We had known that this diagnosis method have probability of 79.7%. It was confirmed that there are close correlations between Iris Signs and Chief Complain and between Iris Signs and Past History.